Pengaruh Kendaraan Berat Terhadap Kinerja Ruas Jalan R.E. Martadinata Palu Dengan Menggunakan Model Hubungan Volume, Kecepatan, Dan Kepadatan Lalu Lintas - Aliviani, Ratika (Jurnal Sains dan Teknologi Tadulako, 2025)
There are three characteristics of traffic flow on a road section that are used as parameters to analyze the behavior of traffic moving on it, namely, Speed ​​- Volume and Density of traffic flow. To represent the mathematical relationship between volume, speed, and traffic density, three models are used as follows: Greenshield, Greenberg, and Underwood. The purpose of this study is to describe the relationship between volume, speed and density of traffic flow on the R.E. Martadinata Palu road section, provide an assessment of the performance of the road section and analyze the effect of heavy vehicles on existing conditions. The results of the analysis of the three models above based on statistical analysis and characteristics in the field, the initial conclusion is that the Greenberg relationship model provides the best results to describe existing conditions. The Greenberg model provides a coefficient of determination value of r2 = 0.76 for conditions with heavy vehicles and r2 = 0.82 for conditions without heavy vehicles, with Vmaks values ​​for each condition of 1725 smp/hour and 1534 smp/hour with an estimated model capacity decreasing by 11.07% from conditions with heavy vehicles to conditions without heavy vehicles. This shows that the model capacity value is influenced by the amount of traffic volume. With the 1997 MKJI method, the DS value with HV = 0.56 and DS without HV = 0.53 are then obtained, which illustrates that the RE.Martadinata road section is still far from saturated conditions that cause queues at peak traffic.